Magnetic anisotropy of FE X NI 100−X nanotubes depending on their composition - Shumskaya, A.E. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Magnetic anisotropy of FE X NI 100−X nanotubes depending on their composition